Os poemas do livro negro de Casimiro de Abreu - Pedronero, Guilherme Carraro (Universidade Federal de São Carlos, 2024)
This research aimed to propose an integrative reading of the literary work Primaveras (1859), by Casimiro de Abreu, focusing on the analysis of the six poems which compose its last subsection, entitled Livro Negro. As a starting point, a bibliographical research has been carried out, focusing on the critical fortune of Casimiro’s work, in order to highlight the fragmentary and reductive reading to which the collection Primaveras has been subject, largely due to the systematic devaluation of the Livro Negro by part of the critics. Through the analysis of the poems of the mentioned section, in conjunction with the other parts of Primaveras, the existence of a poetic project has been highlighted and the Livro Negro, a necessary conclusion to the thematic progression that permeates the book, has been organically reintegrated into the body of work to which it belongs: a meaningful whole whose parts communicate and resonate with each other.
The poems from the black book by Casimiro de Abreu
Keywords: Literatura brasileira; Romantismo; Primaveras; Livro negro; Brazilian literature; Romanticism; Primaveras; Livro Negro; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA